Reduction of environmental impacts of heat pump usage with special regard on systems with borehole heat exchangers - Tamás Buday (Acta Geographica Debrecina. Landscape & Environment Series)
Ground coupled heat pump systems are suitable for extracting subsurface thermal energy with low environmental impact especially regarding CO2 emission. The efficiency of such systems strongly depends on the temperature of the ambient heat (thus underground substrate). This temperature usually changes unfavourably during operation and efficiency becomes lower than the nominal value. Appropriate installation and operation cause lower temperature drop, thus higher efficiency. Consequently, it means lower electricity demand, therefore lower specific CO2 emission, more CO2 saving and lower operation costs. Quantitative analysis with 21 heat extraction models presented in the paper points out that the differences could be significant (up to 30 %), in addition using bivalent mode the environmental impact of the installation or/and operation can be reduced as well, especially using biomass firing as auxiliary heating.